THE ROLE OF CULTURAL COMPETENCE IN ENGLISH LANGUAGE TEACHING: PERSPECTIVES FROM LANGUAGE INSTRUCTORS AND STUDENTS - Devi Saniati; Intan Fangesti; Delastin (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
This study explores the role of cultural competence in English language teaching (ELT) from the perspectives of and students. In the era of globalization, English language skills encompass not only linguistic abilities but also cultural understanding. Cultural competence is crucial for enhancing communication skills and understanding the socio-cultural context of language use. The study employs a qualitative methodology with a case study approach instructors, including interviews, focus group discussions, classroom observations, and questionnaires to gather data. The findings indicate that both instructors and students recognize the importance of cultural competence in language teaching. Instructors with high cultural competence can create an inclusive and supportive learning environment. However, challenges such as limited resources, lack of training, and time constraints often hinder the effective integration of cultural competence in teaching practices. The study emphasizes the need for cultural competence training for instructors to foster a more effective and inclusive learning environment.